IDENTIFIKASI TINGKAT PEMAHAMAN KONTRAKTOR TERHADAP BIM (BUILDING INFORMATION MODELING) DI RUANG LINGKUP KOTA BALIKPAPAN - Raftonado Situmorang; Oryza Lhara Sari; Amirul Mu'minin Al Goviqqih (Racic : Rab Construction Research, 2023)
Currently, in Indonesia the world of construction is growing rapidly, then there is an increasing need for technology to streamline and streamline work in the construction sector. To overcome this, a system called Building Information Modeling (BIM) was created. Compared to conventional methods, the BIM system integrates construction work that can save time and money. To find out the obstacles of contractors in using BIM, this research was conducted to find out the level of understanding of contractors towards BIM and inhibiting factors in implementing BIM. The object of this research is contractors in Balikpapan City, both state-owned and private. By analyzing from various literature and respondents' sources, which make the foundation of this research takes place. In decision making of BIM implementation in Balikpapan City, the results of this research can be considered. The results of the research data analysis and discussion regarding the level of understanding as well as implementation barriers and solutions provided are the results obtained. In implementing the use of BIM, the level of understanding of contractors and practitioners is 0.43 or can be called 43% which means that contractors do not understand BIM. The biggest obstacle in implementing BIM from the analysis of the largest value of 4.4 is the lack of human resources capable of fully operating BIM. Synergizing between all private and state-owned parties to coordinate with each other and provide counseling on the use of BIM in the future is the solution to the obstacles.